0
$\begingroup$

Consider the parabolic equation: $$u_t-k(\Delta u+\sum\limits_{i=1}^n a_i\frac{\partial u}{\partial x_i}+bu)=0$$ where $a_i,b,k$ are constants and $k>0$. How this equation can be transformed to the heat equation $w_t-\Delta w=0$.

I tried to use substitution to convert it to heat equation. But I found the solution to the problem $$u_t-k(\sum\limits_{i=1}^n a_i\frac{\partial u}{\partial x_i}+bu)=0$$ is hard to represent.

Is there any easy ways to do this? Thanks so much!

$\endgroup$
0
$\begingroup$

The change $u=e^{-kbt}v$ will get rid of the $0$ order term. Then the change $w=v(x-k\,a_1,x_1,\dots,x-k\,a_n\,x_n,t)$ will get rid of the first order terms.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.